If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y = 8 + -3y Solving 1y = 8 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 1y + 3y = 8 + -3y + 3y Combine like terms: 1y + 3y = 4y 4y = 8 + -3y + 3y Combine like terms: -3y + 3y = 0 4y = 8 + 0 4y = 8 Divide each side by '4'. y = 2 Simplifying y = 2
| 2(x+4)=2(10x+1) | | x^2-5kx+5k-1=0 | | 3x=0.10-x | | 5xt-2xt= | | z^4=4i | | 3p+2q=5 | | x/5=36/20 | | x/4-2/5 | | 3.67=log(x) | | 4d+3=d-6 | | 2m-6=m+2 | | x^2-x-1=2x+1 | | X^2+28x=16 | | 12-(5x+3)+7(x+1)=8-2x | | logx=-0.45 | | 60+-25x=35x+20 | | t^2-5t-5=0 | | 14y+y^2+48=0 | | 2=sinx | | y=2((sinx)) | | 70=-7(-2-2x-z) | | 2x^2-392=0 | | 1400+s=2100 | | 70=-7(-2-2x-28) | | 5x+4=10-3x | | log(0.5)48=x | | 0,8x=0,6 | | y-7y+5y+10y-6y= | | x+(x+1)+(x+2)+(x+3)+(x+4)=38 | | -x+8=87 | | 4x-3y-17=0 | | -2x-6=21 |